Re-searching Margins : Ethics, Social Justice and Education. - Sanjakdar, Fida.; Keddie, Amanda; Fletcher, Gabrielle; Whitburn, Ben. ([Place of publication not identified] : Routledge, 2022)
Identity, power, and positionality play crucial roles in designing and implementing research critically and ethically across marginalized cultures and communities. Through four unique case studies, this book highlights the dilemmas faced by researchers in the field of education, demonstrating how they grapple with the ethics of research and with their role in the process. Re-searching Margins: Ethics, Social Justice and Education attends to research in four specific marginalised communities, while also engaging in a wider dialogue about the complex theories, methodologies and practices of ethical research in communities of difference. This book examines ethical research with cultures and communities as an exchange in which both the researcher and the researched bring complex contextual and biographical factors shaped by their histories, identities and experiences. Drawing on the lives and research of four renowned scholars, this book will be of interest to researchers and policy makers in education who seek to engage ethically and justly with marginalised communities.
1. Re-searching Margins: An IntroductionFida Sanjakdar 2. Select Literature: Re-view|Re-newGabrielle Fletcher and Ben Whitburn3. Research Narrative 1Islam, Muslim communities, sexuality education and schooling: A delicate balancing actFida Sanjakdar 4. Research Narrative 2A Story/ing of Ethics: Navigating Connection, Obligation and Mess as Re-inventionGabrielle Fletcher5. Research Narrative 3A feminist approach to research ethics: How does a white, atheist, feminist engage in research with Muslim women?Amanda Keddie6. Research Narrative 4Ethical research in Disability studies in educationBen Whitburn7. Working towards ethical research: A DiscussionFida Sanjakdar8. Conclusion: Where to from here?Amanda Keddie
Keywords: Social sciences -- Research; EDUCATION / General